INDIGENOUS KNOWLEDGE SYSTEMS VIN URBAN PLANNING: SCIENTIFIC INTEGRATION OF PAPUAN TRADITIONAL WISDOM IN CONTEMPORARY CITY DEVELOPMENT - Lazarus Ramandei; Rasi Kasim Samosir (International Journal of Multidisciplinary Reseach, 2026)
This study examines the integration of indigenous knowledge systems (IKS) from Papuan communities into contemporary urban planning frameworks in Jayapura, the capital city of Papua Province, Indonesia. Rapid urbanization in Papua has created significant tensions between modern city development paradigms and the deeply rooted traditional wisdom of indigenous Papuan peoples, including the Sentani, Tobati-Enggros, and Ormu communities. Employing a qualitative research methodology with ethnographic and participatory approaches, the study explores how traditional ecological knowledge, spatial cosmologies, and community governance structures can be scientifically operationalized within urban master plans. Data were collected through in-depth interviews with community elders, urban planners, and local government officials, supplemented by field observations and document analysis. Findings reveal that Papuan indigenous knowledge offers robust frameworks for sustainable land use, water management, and social cohesion that are largely overlooked by conventional planning instruments. The study concludes that a decolonizing approach to urban planning, one that systematically incorporates indigenous epistemologies as co-equal knowledge systems, can produce more culturally responsive, ecologically sustainable, and socially just cities in Papua. Policy recommendations for institutional mechanisms to formalize this integration are provided.